STUDI TENTANG PERISTILAHAN DALAM BAHASA INDONESIA YANG TIDAK TERBACA OLEH MAHASISWA SEMESTER II PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVET BANTARA SUKOHARJO - Sudiyana, A (STILISTIKA, 2012)
STUDI TENTANG PERISTILAHAN DALAM BAHASA INDONESIAYANG TIDAK TERBACA OLEH MAHASISWA SEMESTER IIPROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIAFKIP UNIVET BANTARA SUKOHARJOA.     SudiyanaPendidikan Bahasa dan Sastra IndonesiaFKIIP Universitas Veteran Bangun Nusantara Sukoharjo, Jl. S. Humardani, Jombor Sukoharjo                                                             Abstract This study aimed to: 1) obtain the classification of the term of the respondents do not read, 2) know the comparison between theterms of reference books unreadable by Big Indonesian Dictionary, 3) know the inventory of terms that were illegible. The research method used is qualitative descriptive. Returns the sample of respondents is done by random sampling or randomsampling. Data was collected through a survey and inventorytechniques. Results and discussion showed that these terms arenot readable by the Student Education Program Language andLiterature  Indonesia FKIP Nusantara University Veteran BuildSukoharjo second semester of 2009 - 2010 can be classifiedaccording to term (a) the source of the source of the Indonesian language, resources and cognates of foreign language sources, (b) based on its shape, namely the singular, berafiks shape, andform a joint; (c) by kebakuan his writings, namely standard formterms and terms nonbaku form, and (d) based on its formation,the formationof  the appointment (adoption ), with absorption(absorption), and  the translation (translation) and theabsorption-translation (absorption - translation). Keywords: study Indonesian language terminology is not legible, the student